2008
DOI: 10.1111/j.1467-9280.2008.02172.x
|View full text |Cite|
|
Sign up to set email alerts
|

Gaining Control: Training Executive Function and Far Transfer of the Ability to Resolve Interference [retracted]

Abstract: This article has been retracted by both of the authors. During further extension of this work, it was discovered that a mistake had been made in the programming of the working memory training tasks used in this study. This error resulted in the presentation of repeated trial sequences, which were then practiced repeatedly over the 8-day training period. This practice likely resulted in learning of the sequences, rather than training of interference control as we had originally inferred. The first author takes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 33 publications
5
86
1
1
Order By: Relevance
“…Others have shown that WM training benefits are not task specific, but rather, that they extend beyond the trained task by affecting WM processes, including interference buffering (Persson & Reuter-Lorenz, 2008) and WM updating (Dahlin et al, 2008). A few tantalizing studies have further demonstrated transfer of WM training to other assessments of cognition, including measures of cognitive control (Klingberg et al, 2005) and fluid intelligence (Jaeggi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that WM training benefits are not task specific, but rather, that they extend beyond the trained task by affecting WM processes, including interference buffering (Persson & Reuter-Lorenz, 2008) and WM updating (Dahlin et al, 2008). A few tantalizing studies have further demonstrated transfer of WM training to other assessments of cognition, including measures of cognitive control (Klingberg et al, 2005) and fluid intelligence (Jaeggi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, others have demonstrated that WM training can impact domain-general cognitive control mechanisms (Klingberg et al, 2005;Klingberg, Forssberg, & Westerberg, 2002), interference resolution processes (Persson & Reuter-Lorenz, 2008), WM updating processes (Dahlin, Neely, Larsson, Bäckman, & Nyberg, 2008), and even general fluid intelligence (Jaeggi et al, 2008).…”
mentioning
confidence: 99%
“…For instance, in one study using a multifaceted training program (COGITO), participants improved on untrained WM measures including "Animal Span" and the 3-back task (Schmiedek et al, 2010). In some studies, training-related gains are also found in tasks intended to index specific component processes of WM, such as updating or interference buffering (Persson & Reuter-Lorenz, 2008). Similar results, which are summarized under the column "Temporary Memory" in Table 1, suggest that like strategy training, core training produces clearly demonstrable improvements in tasks that directly involve the retention and retrieval of temporarily stored information.…”
Section: Core Trainingmentioning
confidence: 99%
“…An alternative approach is to use a "control training" group, which matches the treatment group on time and effort invested, but is not expected to benefit from training (groups receiving control training are sometimes referred to as "active control" groups). For instance, in Persson and Reuter-Lorenz (2008), both trained and control subjects practiced a common set of memory tasks, but difficulty and level of interference were higher in the experimental group's training. Similarly, control training groups completing a non-adaptive form of training (Holmes et al, 2009;Klingberg et al, 2005) or receiving a smaller dose of training (one-third of the training trials as the experimental group, e.g., Klingberg et al, 2002) have been used as comparison groups in assessments of Cogmed variants.…”
Section: Alternative Interpretations Of Training Gainsmentioning
confidence: 99%
“…-Retracted by authors (Persson & Reuter-Lorenz, 2008) Studies included in meta-analysis (n = 23 studies, 30 independent group comparisons)…”
Section: Included Eligibilitymentioning
confidence: 99%